PELATIHAN DESAIN GRAFIS SEBAGAI STRATEGI PENGUATAN KAPASITAS KREATIVITAS DAN LITERASI VISUAL MAHASANTRI - Muhammad Zia Alghar; Muhammad Irfan Afandi; Fahmi Ishaqi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Graphic design skills are important for students in the digital age. However, students at UPKM El-Ma'rifah UIN Maulana Malik Ibrahim Malang still face limitations in their theoretical and technical understanding. This community service program aims to enhance the graphic design capabilities of students through structured training based on the observe, imitate, modify method. The program was implemented using a hybrid training and empowerment model, attended by 37 students on November 2, 2024. Evaluation was conducted using pre-test and post-test instruments to measure participants' cognitive understanding and satisfaction. The results of the community service showed a significant increase in participants' understanding of graphic design, with an average score increasing from 2.7 (pre-test) to 4.1 (post-test), an increase of 51.9%. The indicators with the highest increase were understanding of the concept of negative space (62.5%) and the principles of color aesthetics (60.0%). The participants' satisfaction level with the training was 94.6%. The majority of participants stated that the training provided technical insights that they did not obtain during their self-taught graphic design learning. This community service contributed to strengthening the creative capacity of students to produce professional and competitive visual content in the digital era.